Exploring a faith-led open-systems perspective of stewardship in family businesses - Carradus, Angela (Journal of business ethics, 2020)
The purpose of this study is to examine how faith-led practices in family firms affect organizational stewardship. Current studies highlight the relevance of religious adherence for family businesses, yet provide limited understanding of how this shapes the key traits of these organizations. Drawing on six autobiographies of family business leaders who openly express their adherence to their faith, and adopting an open-systems analysis of these autobiographies, we demonstrate that faith-led values influence organizational and leadership practices. Overall, our study suggests that the influence of religious beliefs in the organizational practices of family businesses have greater repercussions than previously thought. By introducing a faith-led approach to stewardship, we enrich the theoretical discussion around stewardship and the relevance of religion in family business.